[Group on Beach on Snæfellsnes Peninsula] - Streng, Evelyn Fiedler (1975)
Photograph of a group of people on a beach on Snæfellsnes Peninsula. The sandy beach covers the bottom half of the photograph, leading to a grassy ledge ahead where a group of people stand and sit around. Black rocks are scattered along beach to the right.